Notas autobiográficas de cerâmica e educação: um percurso entre terra e rio, corpo e natureza - Amaral, Suely Rodrigues (Brasil, 2024)
This research starts from a reflection on my creative processes in the fields of art and education, but specifically ceramics, based on my life experiences in the Amazon territory. The forms present in this environment transform all the time, as it is rich in movements and mutations, where I find the ways to develop my poetics. This study reflects on my formative path in life, education and art, in addition to dialoging with productions by other women artists who maintain this very close relationship with their place of origin, with art and nature in their creative processes as the artists Ana Mendieta, Maria Martins and Rosana Paulino. It was after becoming aware of this path of research and creation that I now teach free ceramics workshops in the city of Parintins, in the State of Amazonas. I hope that sharing my journey strengthens other women to believe in themselves and dare other ways of learning and teaching from their places and their life stories.